Ius Constituendum Criminal Law Sanction System with Double Track System Principle in the National RKUHP - Gunawan, Teng Junaidi (SASI, 2022)
Introduction: As the ius constituendum of criminal law, the RKUHP introduces the concept of a double track system in its criminal system. The purpose of this double track system concept is to regulate 2 (two) types of sanctions, namely penal sanction (straf/punishment) and treatment sanction (maatregel/treatment).Purposes of the Research: First, the ratio legis criminal law sanctions system with the principle of a double track system and factual policies in the National RKUHP. Second, the ideal model of the criminal law sanction system has the principle of a double track system in the National RKUHP.Methods of the Research: The research method used in this research is normative legal research. Conduct a study of the Criminal Code and the National RKUHP as well as an analysis of the theory of punishment, especially on penal sanction and treatment sanction.Results of the Research: The results of this study reveal that philosophically the emergence of the double track system concept is influenced by the development of the flow in criminal law, namely from the classical to the modern school, and the neo-classical school. Then the sentencing policy in the National RKUHP is not yet fully based on the principle of a double track system. So that we need an appropriate conception and in accordance with the basic idea of the actual double track system concept, one of which is by integrating additional forms of penal sanction into treatment sanction.